Colchicine combination therapy increases treatment tolerance in patients with arthritis: A systematic review and meta-analysis. - Changwei Zhao; Xiaogang Hao; Wenjun Cai; Ling-Feng Zeng; Wenhai Zhao; Xiangxin Li (PLoS ONE)
Background Arthritis seriously affects people's quality of life, and there is an urgent clinical need to improve the efficacy of medications as well as to reduce the adverse effects induced by treatment. Combined colchicine therapy is gradually being embraced in clinical care, but the evidence remains insufficient. Methods English databases were searched from the establishment to September 4, 2024. Eleven eligible Randomized controlled trials (RCTs) were included. The quality of the literature was assessed by the risk of bias tool in the Cochrane Handbook. Relative risk (RR) and Cohen's d (SMD) were used for categorical and continuous variables, respectively, at 95% confidence interval (CI), and Stata 17.0 software was used for statistical analysis. Sensitivity analyses were used to verify the stability of the analyzed results, and heterogeneity analyses were used to explore the sources of heterogeneity in the studies. Funnel plots and Egger's test were used to assess publication bias. Results Eleven eligible RCTs were included in this study. Compared with conventional treatment, combined colchicine treatment improved patient's global assessment results (SMD = 1.24, 95% CI [0.01, 2.47], P = 0.05, I2 = 0]), stiffness (SMD = -0.81, 95% CI [-1.43, -0.19], P = 0.01, I2 = 63.91%]) and did not increase adverse effects (RR = 0.79, 95% CI [0.31, 1.27], P = 0.36, I2 = 0.00%). However, combined colchicine treatment did not improve visual analog scores (VAS) (SMD = -0.96, 95% CI [-2.85, 0.93], P = 0.13, I2 = 97.99%]), Western Ontario and McMaster Universities Arthritis Index (WOMAC) pain (SMD = 0.01, 95% CI [-0.24, 0.27], P = 0.91, I2 = 0]), WOMAC function (SMD = -0.01, 95% CI [-0.36, 0.16], P = 0.44, I2 = 0]), Total WOMAC scale (SMD = -0.05, 95% CI [-0.33, 0.22], P = 0.70, I2 = 0]), physician 's global assessment (SMD = 0.36, 95% CI [-2.27, 3.00], P = 0.79, I2 = 97.04%]) and Modified Clinical Health Assessment Questionnaire (ModHAD) (SMD = -1.72, 95% CI [-4.90,1.45], P = 0.29, I2 = 99.11%]). Conclusion Compared with colchicine alone, combination therapy improves patients' quality of life without increasing the incidence of adverse events.